2014
DOI: 10.1111/pme.12475
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Abuse and Tampering in the United States: Results of a Self-Report Survey

Abstract: Tampering with opioid medications to get high is associated with substantial loss of productivity and health care use. Technologies that reduce users' ability to tamper may reduce the burden of opioid abuse on the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
(24 reference statements)
2
24
0
Order By: Relevance
“…This finding corroborated an analysis of the National Health and Wellness Survey, which also found that higher income was associated with opioid abuse (Vietri et al, 2014). Furthermore, other studies have found that student disposable income is a risk factor for adolescent use of alcohol, tobacco, hookah, marijuana, ecstasy (MDMA, “Molly”), synthetic marijuana, “bath salts”, and cocaine (Martin et al, 2009; Scragg et al, 2002; Zhang et al, 2008; Palamar, 2015; Palamar et al, 2015a, 2015b).…”
Section: Discussionsupporting
confidence: 85%
“…This finding corroborated an analysis of the National Health and Wellness Survey, which also found that higher income was associated with opioid abuse (Vietri et al, 2014). Furthermore, other studies have found that student disposable income is a risk factor for adolescent use of alcohol, tobacco, hookah, marijuana, ecstasy (MDMA, “Molly”), synthetic marijuana, “bath salts”, and cocaine (Martin et al, 2009; Scragg et al, 2002; Zhang et al, 2008; Palamar, 2015; Palamar et al, 2015a, 2015b).…”
Section: Discussionsupporting
confidence: 85%
“…In a survey of 25,864 patients, older age was also associated with lower odds of prescription opioid abuse [24].…”
Section: Discussionmentioning
confidence: 99%
“…[15,28,30] Available data suggest that men are more likely than women to abuse prescription opioid analgesics. [31,[67][68][69] Men also appear to be more likely than women to abuse prescription opioid analgesics via non-oral routes (e.g., snorting or injection) (Figure 4). [28,67,70] Other clinically relevant gender differences in patterns of abuse have also been noted.…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…[6,11,[22][23][24][25][26][27][28][29][30][31] Comprehensive data on methods of manipulation and routes of abuse of prescription opioid analgesics have been generated through the US National Health and Wellness Survey. [31] The prevalence of prescription opioid analgesic abuse in the 3 months before the survey was estimated at 1.3% of the adult population in the USA. Most (91%) of the 225 abusers of prescription opioid analgesics who completed the survey reported taking the abused formulation via the intended route of administration.…”
Section: Frequency Of Different Routes Of Abusementioning
confidence: 99%